The Molecular Structure of Yeast Phenylalanine Transfer RNA in Monoclinic Crystals - Quigley, G. J. (1974)
The molecular structure of monoclinic crystals of yeast phenylalanine tRNA is analyzed by comparing it to the orthorhombic crystals of the same material whose structure has been determined. Changing the packing of the molecule from the head-to-head, tail-to-tail arrangement in the orthorhombic lattice to a head-to-tail packing makes it possible to generate a proposed structure for the monoclinic unit cell. The structure factors for the proposed arrangement have been calculated and compared with those experimentally observed from monoclinic crystals. The residuals from this comparison are low enough to conclude that at 4-Å resolution, the three-dimensional structure of the molecule in the monoclinic crystal is essentially the same as that in the orthorhombic crystal. In addition, a correlation coefficient calculated from intensities based on a skeletal model of the molecule also confirmed the structure in the monoclinic cell. Electron density difference maps, as well as the presence of close contacts in the anticodon loop region of the monoclinic crystal, suggest that the anticodon loop may have a slightly different conformation than that observed in the orthorhombic crystals.